Converging and Diverging Points of Indigenous Education and Formal Education Systems in Nepal: A Case of Tharu Community - Niure, Dhruba Prasad (Interdisciplinary Research in Education, 2019)
This study was carried out to explore the converging and diverging points of indigenous education and formal education systems of Nepal. The entire research process of the study was guided by the interpretive-constructivist paradigm followed by a case study design. Tharu teachers and students were chosen as a sample by using a purposive sampling method and then in-depth interviews, focus group discussion, and document analysis was used as the main methods of garnering intensive information regarding the similarities and differences of indigenous education and formal education systems primarily in reference to Tharu community. Study results reveal that both formal and indigenous education systems have their own educational goals, curriculum, teachers, and both of them impart particular knowledge and skills to the learners by using certain instructional techniques. Nevertheless, both education systems are not identical to each other in terms of learning environment, skills-focused, nature of learning, type of teachers, the medium of instruction, and assessment devices. As a result, Tharu children show poor academic performance within the formal education system as compared to non-indigenous children. Coherence between formal curricular contents and indigenous knowledge should be made to provide relevant and effective educational services to indigenous children within formal educational institutions for the purpose of improving their living standards in the future through quality education.